2005
DOI: 10.1080/15459620590949020
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Private Sector Respirator Use in the United States: An Overview of Findings

Abstract: Limitations of previous surveys of respirator use led the National Institute for Occupational Safety and Health (NIOSH) and the Bureau of Labor Statistics to undertake a survey of respirator use and practices among U.S. private sector employers. The survey was mailed to 40,002 private sector establishments in August 2001; the responses were used to develop national estimates. Respirator use was required in 4.5% of establishments and for 3.1% of employees. Of the establishments requiring respirator use, 95% use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Respiratory protection is the most widely used preventive measure against dust in the construction industry [Tjoe et al, 2003;Doney et al, 2005] ]. These findings suggested that large numbers of employers may not follow NIOSH recommendations and OSHA requirements for the selection and use of respirators, potentially placing workers at risk [Doney et al, 2005].…”
Section: Industry and Occupationmentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory protection is the most widely used preventive measure against dust in the construction industry [Tjoe et al, 2003;Doney et al, 2005] ]. These findings suggested that large numbers of employers may not follow NIOSH recommendations and OSHA requirements for the selection and use of respirators, potentially placing workers at risk [Doney et al, 2005].…”
Section: Industry and Occupationmentioning
confidence: 99%
“…These findings suggested that large numbers of employers may not follow NIOSH recommendations and OSHA requirements for the selection and use of respirators, potentially placing workers at risk [Doney et al, 2005].…”
Section: Industry and Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…21% (15) Performance 18% (13) Cost 18% (13) Name value of vendor 18% (13) Worker preference 10% (7) Design of respirator 8% (6) Direction by CEO 5% (4) Pressure of union Manufacturers presume that since carbon fibers adsorb airborne chemicals, this mask can be used as a substitution for a gas/vapor respirator, but this mask should not be used for that purpose such as purifying high concentration of airborne chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…This survey revealed that twenty-two percent of the workers wore unauthorized dust respirators and seventy-three percent used a knitcover, which seemed to deteriorate face-sealing. In 2001, a survey was undertaken among 40,002 private sector establishments in the United States to ensure that respirator programs adequately protected U.S. workers 4) . In this survey, the authors indicated that the chemicals and allied products manufacturing industry presented a higher potential for worker exposure, thus stimulating more thorough attention to respiratory protection 5) .…”
Section: Introductionmentioning
confidence: 99%